Management of attention-deficit/hyperactivity in a patient with fibular hemimelia - Narravula, Rithika; Gudipati, Pranati; Suthar, Himani; Parikh, Parinda (International Journal of Research in Medical Sciences, 2026)
Fibular hemimelia (FH) is a rare condition defined by the partial or complete absence of the fibula, often accompanied by associated deformities and anomalies, with an estimated incidence of 1 in 40,000 live births. In parallel, attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder marked by patterns of inattention, hyperactivity, and impulsivity that disrupt daily functioning and quality of life. The ADHD medication may influence children with FH, given their shared developmental risk factors. Understanding the interplay between these conditions is vital for developing comprehensive care strategies that address both the physical and behavioral challenges faced by these individuals. This case describes an 8-year-old male with ADHD and anxiety linked to FH. The patient faced challenges in learning, reading and attention, along with disruptive behaviors and feelings of bullying from peers. Evaluation indicated appropriate hygiene, a linear thought process and mild anxiety, with the patient describing his mood as “okay.” As a part of his treatment plan, the patient was prescribed 18 mg of methylphenidate HCl daily, 15 mg of L-methylfolate and referred for psychological testing. The intersection of FH and ADHD presents clinical challenges that require a nuanced understanding of both conditions. FH can result in significant limb discrepancies and may necessitate orthopedic interventions, while ADHD is often treated with stimulant medications that, while effective, can have side effects including potential impacts on growth. This highlights the importance of monitoring growth in children with both conditions, as stimulant use may influence physical health outcomes. Upon follow up, the patient demonstrated improved attention and behaviour, with no evidence of growth suppression.